2010
DOI: 10.1007/s11224-010-9641-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies on zwitterionic (E)-2-(1-(2-(4-methylphenylsulfonamido)ethyliminio)ethyl) phenolate

Abstract: The Schiff base compound (E)-2-(1-(2-(4-methylphenylsulfonamido)ethyliminio)ethyl) phenolate has been synthesised and characterized by IR, UV-Vis, and X-ray single-crystal determination. Ab initio calculations have been carried out for the title compound using the density functional theory (DFT) and Hartree-Fock (HF) methods at 6-31G(d) basis set. The calculated results show that the DFT/B3LYP and HF can well reproduce the structure of the title compound. Using the TD-DFT and TD-HF methods, electronic absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…From Table 4, we can conclude that the total molecular energies obtained by the IEF-PCM method decrease with the increasing polarity of the solvent, while the dipole moments and chemical hardness will increase with the increase of the polarity of the solvent. According to these results, the stability of the title compound increases in going from the gas phase to the solution phase [62].…”
Section: Energetics and Stabilitymentioning
confidence: 84%
“…From Table 4, we can conclude that the total molecular energies obtained by the IEF-PCM method decrease with the increasing polarity of the solvent, while the dipole moments and chemical hardness will increase with the increase of the polarity of the solvent. According to these results, the stability of the title compound increases in going from the gas phase to the solution phase [62].…”
Section: Energetics and Stabilitymentioning
confidence: 84%
“…The weak bands in the range 3033-3000 cm -1 correspond to the symmetric and asymmetric stretching vibrations of aromatic CH bonds. The characteristic region of 1500-1700 cm -1 can be used to identify the proton transfer of Schiff bases [48]. The title compound shows a strong band at 1620 cm -1 which is assigned to C=O stretching vibration [49].…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…In the experimental paper by Alpaslan et al [256], synthesis, characterization, and X-ray single crystal structure determination of (E)-2-(1-(2-(4-methylphenylsulfonamido)-ethyliminio)ethyl) phenolate is reported. The results have shown that the compound exists in the zwitterionic form, which is stabilized by the intramolecular N ?…”
Section: Issuementioning
confidence: 99%